Bessel Function in Galois Fields - Ubolsri, Patchara; Laohakosol, Vichian; Kongsakorn, Kannika (Agriculture and Natural Resources, 2001)
Analogues of Bessel functions in function fields of nonzero characteristic are investigated. Certain basic properties , are derived. It was found that (i) their domain and range are contained in the whole universe, (ii) basic recurrence relations hold, (iii) they are not one - to - one, and (iv) they are linear and have generating function.